Analysis of Relation Between Electroclinical Features and Cerebrospinal Fluid Antibody Titers in Patients With anti-NMDAR Encephalitis. (January 2019) - Miao, Ailiang; Du, Mingyang; Wang, Lingling; Ge, Jianqing; Lu, Hengdong; Xu, Haiyan; Liu, Hongxing; Yu, Chuanyong; Wu, Caiyun; Gao, Yuan; Sun, Jintao; Shi, Qi; et al.
Purpose . This study aimed to determine the relation between electroclinical features and cerebrospinal fluid (CSF) antibody titers in patients with anti- N -methyl-d -aspartate receptor (anti-NMDAR) encephalitis. Method . Clinical symptoms and electroencephalography (EEG) at different stages were analyzed in 51 hospitalized patients with anti-NMDAR encephalitis. Results . Behavioral changes were the initial symptoms in 90.9% (20/22) of female patients with high (1:10 or 1:32) CSF antibody titers. A greater number of clinical symptoms were observed in the patients with high CSF antibody titers than in those with low (1:1 or 1:3.2) CSF antibody titers (mean 3.11 ± 1.06 vs 1.62 ± 0.65, P = .000). The number of clinical symptoms was greater in the female patients than in the male patients (mean 3.52 ± 0.98 vs 2.69 ± 1.09, P = .000). At the peak stage, worse background activity (BA) in EEG recordings was observed in patients with high CSF antibody titers than in those with low CSF antibody titers (Mann-Whitney U test, P = .001). The peak-stage BA in EEG was worse in female patients than in male patients (Mann-Whitney U test, P = .000). Modified Rankin scale scores were higher in patients with high CSF antibody titers than in those with low CSF antibody titers (mean 2.62 ± 1.42 vs 0.75 ± 0.97, P = .000). Brush patterns and constant chewing were observed primarily in female patients with high CSF antibody titers. Epileptic discharges were located predominately in the frontal regions and were noted to vary. Conclusion . The electroclinical features of patients with anti-NMDAR encephalitis were associated with gender and CSF antibody titers.